Forward Shifting of a Payroll Tax Under Monopolistic Competition - Arnold, Sam (Quarterly Journal of Economics, 1947)
I. The incentive argument for merit rating, 267. — Definitions, 268. — II. Monopoly profit before and after the imposition of contribution costs, 269. — Implications for forward shifting of contribution costs, 270. — III. Adequacy of profit reductions, 274. — Effect of different contribution rates upon a given monopolist, 274. — Effects of elasticities of demand and slopes of marginal cost functions, 276. — Conclusions, 283.